2017
DOI: 10.1111/bju.14020
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy after radical nephroureterectomy does not improve survival in patients with upper tract urothelial carcinoma: a joint study by the European Association of Urology–Young Academic Urologists and the Upper Tract Urothelial Carcinoma Collaboration

Abstract: Adjuvant chemotherapy did not improve OS compared with observation in the present study. These results contribute to the uncertainties regarding postoperative chemotherapy in UTUC, and suggest dedicated prospective trials, new more potent therapies, and the identification of enhanced patient selection criteria are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 30 publications
0
36
2
Order By: Relevance
“…Perioperative systemic therapy might be beneficial in locally advanced UTUC, but it is still a controversial issue. 6,[20][21][22] Different etiologies might be associated with different tumoral mutations, and we still do not understand whether the benefit of systemic therapy can be observed in different populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perioperative systemic therapy might be beneficial in locally advanced UTUC, but it is still a controversial issue. 6,[20][21][22] Different etiologies might be associated with different tumoral mutations, and we still do not understand whether the benefit of systemic therapy can be observed in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…There is an unusual presentation of high prevalence and female predominance for upper UTUC in the Taiwan and China area . In other Asian areas, such as Japan and Korea, European and American countries, the male:female ratio is from 1.223:2.860 . However, the male:female ratio in Taiwan and China is 0.773:0.838 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there might be several additional biases of patient selection that might have affected the observed outcomes, and such factors cannot be fully acknowledged retrospectively, even with application of advanced statistical methods, similar to what we have recently experienced in another context. 18 Additionally, data in the RISC data set were mainly provided by oncologists, therefore it is likely that the RISC population suffered from an unavoidable enrichment in patients with the poorest outcome. This might the reason why the proportion of locoregional relapses was close to the upper bound of the range reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of perioperative chemotherapy for patients treated with NU remains controversial. A cohort study of patients fit enough to receive systemic chemotherapy for metastatic UTUC reported an overall survival (OS) benefit to combine chemotherapy and NU (4), while a recent multi-center study found that adjuvant chemotherapy after NU did not improve OS compared to observation (5). This may result from the dilemma to determine which types of patients are suitable for perioperative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%